MODEL PENGEMBANGAN AGROWISATA PEDESAAN SEBAGAI BASIS PEMBANGUNAN MASYARAKAT (KAJIAN AGROWISATA DI DESA TANJUNG KECAMATAN NGAGLIK KABUPATEN SLEMAN DIY) - SITI SYAMSIAR (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
The aims of this research are: 1) to identify agrotourism potency from physical, social, economic and cultural sides and 2) to analyze agrotourism development model in Tnajung Village, Ngaglik District, Sleman Regency. This research is qualitatif research using descriptif method. Location of this research is agrotourism in Tanjung Village thats taken purposively